Principal Effects on Academic Progress Over Time and the Potential Effects of School Context and Principal Leadership Practices (Journal of School Administration Research and Development, 2021)
We used interrupted time series to examine the causal effect of principals on school performance over time and whether the trajectory of performance is affected by school context and leadership practices.  Results were based on a unique dataset that links responses from the National Schools and Staffing Survey with 10 years of California Academic Performance Index (API) data.  These data and methods address a need identified in the literature to examine the effects of principals with more rigorous research designs.  Results indicated that improved academic performance does not occur immediately but accrues over time.  We estimated both the first-year impact of a principal and the subsequent impact over time.  The effect size increased from 0.04 in the first year to 0.21 by year three.  Exploratory analyses showed that school context and leadership practices account for a substantial portion of the variation in progress among schools: 25% and 40%, for context and practices, respectively.  Although the Schools and Staffing Survey afforded an opportunity to examine teacher and principal responses to academic performance over time, continued study is warranted to systematically and more concretely identify specific leadership practices that impact academic progress over time.